The Relationship Between Aleppo Jews and the Ottoman Administration in The 18th Century (Journal of Hama University, 2020)
The survey aims at bringing out a real image about the Jewish life in the province of Aleppo in the 18th century when it was a part of the Ottoman state.Did the Jews perform their religious rituals without harassment in that district?  were they representing the role of the real citizenship? Or did they cause real problems to the Ottoman state through that period of time?The survey showed that Jewish community in Aleppo was a part of the Aleppian society since they worked in commerce and loan to get loan interests later inside and outside the city of Aleppo. The clan practiced this profession, so all money-changers and brokers were exclusively Jews.The survey pointed to a very significant issue that the Jews hadn’t involved in any military conflicts against the Ottoman state and they hadn’t contributed to fund any military acts either although they were almost causing all problems then.Nothing refers, through the survey, that the Jews were forced to embrace Islam or being harassed in their rites. This indeed rebuts the argument that they were oppressed.